Moderating Role of Brand Trust on Offline vs Online Shoppers and its Impact on Cognitive Dissonance - Tomar, Vivek Singh; Tomar, Rohit Singh; Khattri, Varsha (Indian Journal of Marketing, 2020)
Brand trust plays a decisive role in the choice of a brand during product purchase. It is also well known that online shopping causes higher cognitive dissonance as compared to offline mode of shopping. Trust in the brand has a soothing effect and is thus found to decrease cognitive dissonance. This study was conceived to explore the interrelationship between online and offline shopping, brand trust, and cognitive dissonance. The hypotheses of the study were formalized to investigate the influence of brand trust on cognitive dissonance and the impact of mode of shopping chosen by a customer on cognitive dissonance. The paper also investigated the moderating role of brand trust on both the independent variable (mode of shopping) and dependent variable (cognitive dissonance). A survey was conducted with 302 consumers of mobile phones who had purchased a mobile phone either from an online or offline store. The direct impact and interaction effects of brand trust on cognitive dissonance and mode of shopping were tested using continuous moderation, PROCESS macro of Andrew F. Hayes in SPSS 23. Brand trust displayed a significant moderating effect between mode of shopping, that is, online and offline stores and cognitive dissonance. The findings of the study are found to be critical for multi-channel retailers, particularly those who have their presence in both online as well as brick and mortar store set up.